Ternary Tree Based Approach For Accessing the Resources By Overlapping Members in Cloud Computing - Amar Buchade; Rajesh Ingle (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In cloud computing, immediate access of resources is important due to cost incurred to customer by pay per use model of cloud computing. Usually resource is protected by using cryptography technique. The resource may be shared by multiple members in group. There can be overlapping members to access the multiple resources. Group key management is important to form the group key to access the resource. Group key formation time is crucial for immediate access of protected resource in cloud computing. Thus ternary tree based approach is proposed to form the key for overlapping members accessing resources. Membership event such as join and leave also considered. Through the analysis, it is found that computational overhead is reduced by 23% if ternary key trees are combined than independent ternary key trees. It is also observed that combined ternary key tree outperforms the combined binary key tree approach for group key formation by considering overlapping members. Security requirement analysis of group membership for key formation is also provided in the paper.